Overexpression of Kinesin Associated Protein 3 (KIFAP3) in Breast Cancer - Telikicherla, Deepthi (J Proteomics Bioinform, 2012)
Gene expression profiling studies on breast cancer have generated catalogs of differentially expressed genes. However, many of these genes have not been investigated for their expression at the protein level. It is possible to systematically evaluate such genes in a high-throughput fashion for their overexpression at the protein level using breast cancer tissue microarrays. Our strategy involved integration of information from publicly available repositories of gene expression to prepare a list of genes upregulated at the mRNA level in breast cancer followed by curation of the published literature to identify those genes that were not tested for overexpression at the protein level. We identified Kinesin Associated Protein 3 (KIFAP3) as one such molecule for further validation at the protein level. Immunohistochemical labeling of KIFAP3 using breast cancer tissue microarrays revealed overexpression of KIFAP3 protein in 84% (240/285) of breast cancers indicating the utility of our integrated approach of combining computational analysis with experimental biology.